Peri-procedural outcome of transcatheter interventions for congenital heart diseases in children in a tertiary level hospital in South Tamil Nadu, India - Masaraddi, Sanjay K.; Sukulal, Kiron S.; K. E., Elizabeth; K., Rugmini (International Journal of Contemporary Pediatrics, 2018)
Background: Transcatheter based therapies in congenital heart defects have gained popularity, as the morbidity associated with the correction of these defects has been dramatically reduced. Complication rates in this group of children are low and our centre is striving to achieve the same outcome as other major centres. Objective of this study sought to determine the institutional complication rates in a group of children who underwent transcatheter interventions for their congenital heart disease Methods: This prospective observational study enrolled 125 patients who underwent elective transcatheter cardiac interventions for congenital heart defects between February 2014 and January 2018. Major and minor complications were predefined. Results: The age of these children ranged from 9 months to 18 years (mean age 9.22 years). The success rate was 99.2% (124/125). Few children (16%) had minor procedure related complications. Only 1 child had a major complication. Conclusions: Transcatheter cardiac interventions in children are highly successful. Meticulous planning and proper case selection are the major contributors for the success of any centre.